Gallic acid attenuates diabetic cardiomyopathy by inhibiting ferroptosis and protecting mitochondria via the TSPO/FTMT pathway - Zou, Chenchao; Xu, Huaihan; Hu, Fajia; Yu, Yuxian; Liu, Lanxiang; Wang, Xiuqi; Zhang, Zheyu; Zou, Huaxi; Liu, Jichun; Huang, Huang; Lai, Songqing (Frontiers in Pharmacology, 2025)
PurposeDiabetic cardiomyopathy (DCM), which is diabetes mellitus-induced cardiomyopathy, significantly elevates the risk of heart failure and sudden cardiac death. No specific treatments for DCM are currently available. Gallic acid (GA) is a polyhydroxyphenolic compound that has been shown to inhibit ferroptosis and maintain mitochondrial homeostasis, with potential therapeutic effects in various cardiac diseases. However, its specific role and underlying mechanisms in DCM remain unexplored.MethodsAn in vitro model was established using H9C2 cells pretreated with high glucose plus palmitate, and an in vivo type 2 diabetes mellitus model generated by treating rats with streptozotocin-induced and feeding a high-fat diet. The protective effects of GA and its mechanism of action were evaluated using various methods, including flow cytometry, Western blotting (WB), and transmission electron microscopy. Bioinformatics analysis identified potential target genes for GA’s cardioprotection, which were subsequently validated using pAD/TSPO (for overexpression) and pAD/FTMT-shRNA (for silencing) constructs.ResultsGA treatment decreased PTGS2, lactate dehydrogenase, malondialdehyde, ferrous iron, ROS, and oxidized glutathione disulfide (GSSG) levels and increased cell viability, glutathione (GSH) levels, the GSH/GSSG ratio, and GPX4 protein levels in the injury models. GA markedly attenuated mitochondrial ultrastructural damage and promoted mitochondrial homeostasis. These protective effects were abrogated by TSPO overexpression and FTMT silencing.ConclusionGA was shown to attenuate diabetic cardiomyopathy by inhibiting ferroptosis and protecting mitochondria via the TSPO/FTMT signaling pathway.